Anti-epidemic Measures of Municipal Authorities in Western Siberia in Late XIX — Early XX Centuries - A. I. Tatarnikova (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
The events in the late XIX — early XX centuries in Western Siberia, where the population survived several epidemics of cholera, typhus and typhoid fever, measles and other infectious diseases, are considered. It is noted that the sad result of the outbreak of many infections was the high epidemic mortality of the population. The activity of municipal authorities on the prevention and control of the spread of widespread diseases, the prevention of high mortality among the sick is being studied. The anti-epidemic measures taken by local authorities are analyzed: an increase in expenditures for urban improvement; the publication of mandatory sanitary regulations; creation of medical and sanitary executive commissions; division of the city territory into sections and assignment of sanitary guardians to them; arrangement of bacteriological laboratories, infectious barracks and disinfection chambers; health education of the population. The conclusion is made about positive changes in the prevention and treatment of a number of infectious diseases, the organization of sanitary supervision over the state of water supply sources, places of sale of food, the maintenance of garbage and cesspools, the dumping of sewage on strictly designated areas. At the same time, attention is drawn to the persistence of high epidemic mortality (especially infant mortality) due to the low standard of living of most of the townspeople, malnutrition, poor development of hygiene skills, lack of awareness of the causes and methods of treating diseases.